Lung Cancer and Isolated Adrenal Metastases: Different Disease? - Rodrigo, A. S. Sardenberg; Riad, N. Younes; Marcos, André Costa; Carlos, Henrique A. Teixeira (Journal of Respiratory Diseases, 2019)
Distant metastases generally indicate disseminated disease and the standard treatment for these patients is palliative chemotherapy. Retrospective series showed that selected patients with metastatic lung cancer and a solitary extrathoracic disease could be effectively treated with curative intention by resection of both primary tumor and the single site of metastatic disease. According to current data, adrenalectomy might be considered as an alternative option for patients with isolated adrenal metastases. Significant morbidity and mortality may be happened by these procedures, and a cautious analysis of pros and cons should be discussed with the patient. We present a review of the literature and updated recommendations focusing lung cancer with solitary adrenal metastasis.